Determinants of transcription factor regulatory range - Chen-Hao Chen (Nature Portfolio, 2020)
Characterization of the distance over which TF binding influences gene expression is important for inferring target genes. Here the authors study this relationship using thousands of genomic data sets, finding two classes of TFs with distinct ranges of regulatory influence modulated by chromatin states of topologically associated domains.